Did the Blue Planet set the Agenda for Plastic Pollution? An Explorative Study on the Influence of a Documentary on the Public, Media and Political Agendas. Issue 1 (2nd January 2021) - Males, Jennifer; Van Aelst, Peter
ABSTRACT: Over the last two decades documentaries have been receiving more recognition as a way of influencing public perception and generating discourse about societal problems. Previous studies within the field of communication research have given some attention to the agenda-setting effects of environmental documentaries but have overlooked the issue of plastic pollution. This study addresses this gap in the literature by exploring whether The BBC environmental documentary series, The Blue Planet, set the agenda for plastic pollution in the UK. The research was designed using a combination of both a prominence analysis, measuring the frequencies of plastic pollution-related key terms, and a quantitative content analysis, giving an in-depth study into plastic pollution interest, of internet search data, newspaper articles and political debates. The results show that since the documentary was broadcast, plastic pollution-related terms were mentioned by the media and politicians and searched for online significantly more often than previously. The results also seem to imply that The Blue Planet generated this interest in plastic pollution which was, for both the media and political agendas, long-lasting. These results have implications for understanding the importance of documentaries as a viable source of putting environmental issues on the public, media and political agendas.